ANALYSIS OF THE EFFECT OF POPULATION GROWTH ON ECONOMIC DEVELOPMENT IN ACEH PROVINCE IN 2018-2019 - Alya, Honey; Antika, Reni (Journal of Social Science and Multidisciplinary Analysis, 2024)
This journal aims to analyze the effect of population growth on economic development in Aceh Province in the 2018-2019 period. This study uses primary and secondary data to identify the relationship between population growth and economic development indicators such as Gross Regional Domestic Product (GDP), employment, and investment. The analytical methods used include regression analysis and descriptive analysis to gain a better understanding of the impact of population growth on economic development in the region. The results of this study are expected to provide relevant policy recommendations to ensure inclusive and sustainable economic growth in Aceh Province.